2020
DOI: 10.4041/kjod.2020.50.4.249
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional assessment of nasal changes after maxillary advancement with impaction using stereophotogrammetry

Abstract: Three-dimensional assessment of nasal changes after maxillary advancement with impaction using stereophotogrammetry Objective: To evaluate the changes in the nose in three dimensions after Le Fort I osteotomy in patients with skeletal Class III malocclusion. Methods: The subjects were 40 adult patients (20 females and 20 males; mean age, 20.3 ± 3.0 years; range, 17.0 to 31.1 years) who underwent one-piece Le Fort I osteotomy with maxillary advancement and impaction treatment for maxillary hypoplasia. The mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…21 Generally, it is considered that maxillary advancement surgery leads to nasal tip elevation. 20,22 Coban et al 7 reported a mean upward Prn movement of 1 mm and attributed this to surgical quantity. In the present study, 1.36 ± 1.64 mm upward and 1.55 ± 1.6 mm movement were observed after rotational surgery along y-and z-axes (P value < 0.01) (Supplementary Digital Content, Table 2, http://links.lww.com/SCS/D769).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Generally, it is considered that maxillary advancement surgery leads to nasal tip elevation. 20,22 Coban et al 7 reported a mean upward Prn movement of 1 mm and attributed this to surgical quantity. In the present study, 1.36 ± 1.64 mm upward and 1.55 ± 1.6 mm movement were observed after rotational surgery along y-and z-axes (P value < 0.01) (Supplementary Digital Content, Table 2, http://links.lww.com/SCS/D769).…”
Section: Discussionmentioning
confidence: 99%
“…As the increased number of patients have chosen bi-maxillary orthognathic surgery for esthetic reasons, it is necessary to understand postoperative changes and stability through long-term follow-up. Prior articles [6][7][8] also stated that once the postoperative swelling and edema subsides, the amount of soft tissue changes afterward is not significant in 2D analyses. Therefore, the goal of this study was to evaluate delayed soft tissue changes after clockwise repositioning of the MMC using cone-beam computed tomography (CBCT) and 3D analysis software.…”
mentioning
confidence: 99%
“…24,25 In our study, no significant change was observed in the nasolabial angle after surgery (P=0.933). Similarly, Coban et al 26 evaluated the changes in the nose in three dimensions after Le Fort I osteotomy in patients with skeletal Class III malocclusion concluded that there was no change was observed in the nasolabial angle. In contrast, in another study in which combined anterior segmental osteotomies were performed, it was reported that the nasolabial angle increased by an average of 15.5°.…”
Section: Discussionmentioning
confidence: 99%
“…This method can be used to assess changes in soft tissue and skin surface after orthognathic surgery more accurately than methods such as direct anthropometry, cephalometric photography and 2D photography [ 12 ]. Additionally, this scanner is a fast and reliable device and has an error of 0.2 to 1 mm for clinical use compared to 0.5–1 mm of laser scanners [ 14 ]. Moreover, thanks to this imaging technique, our patients were exposed to lower dose of radiation compared to similar studies using CT scans [ 1 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other advantages of this method include no radiation exposure and high repeatability. It also provides the possibility of volumetric, topographic, regional, and linear evaluations [ 14 ]. This method can be used to assess soft tissue and skin surface alterations after OS more accurately than methods such as direct anthropometry, cephalometric photography, and 2D photogrammetry [ 12 ].…”
Section: Introductionmentioning
confidence: 99%